Evaluation of Sialic Acid Levels in the Umbilical Cord Blood of Newborns of Diabetic and Non-Diabetic Mothers and the Relation with Poor Neonatal Outcome - Yuksel Kurban; İbrahim Uyar; Koza Murat; Murat Alan (Gynecology Obstetrics & Reproductive Medicine)
Objective: The aim of this study is to evaluate sialic acid levels in cord blood samples of infants of natal diabetic and non-diabetic pregnancies and to assess the correlation of sialic acid levels with the poor neonatal outcomes.